Maximizing Youtube as Language Mediated Learning for Undergraduate Students - Imam Fauzi; Wahyuddin Wahyuddin (Globish: An English-Indonesian Journal for English, Education, and Culture, 2026)
The challenge within the education world to fulfill the digital natives is large enough. This is caused by their different life experiences, especially experiences in using technology. The internet itself opens up many possibilities for integrating technology into classroom learning. YouTube is a learning media that can be integrated into learning subjects that students consider difficult. This research aims to see to what extent YouTube can be used as a learning medium in English courses and figures out the effectiveness of maximizing YouTube as a medium in language teaching and learning. The sample of this research is 25 undergraduate students in the second semester of the Management study program. Furthermore, the research data was gathered through a pre-test and post-test to analyze quantitatively the effectiveness of utilizing YouTube as a language learning medium, and a questionnaire to find out students’ perspectives on the utilization of YouTube in language learning situations. The results revealed an increase in the average post-test (66.52 to 84.48). This research proves that video learning materials on YouTube can be used as a learning medium and significantly encourage students' learning outcomes in the language learning process